Effect of Career Guidance on Employee Performance in Kenyan Private Universities: A Case of Religious Based Private Universities - M. Mwova, Annastacia; Langat, Nahashon (International Journal of Scientific Research and Management (IJSRM), 2021)
From the employees’ perspective, the lack of career guiding can lead to frustration, feelings of not being appreciated by the company and not identifying the right position leads to the need of a job change and / or the company. This is particularly more pronounced in such settings as universities, where employee performance determines the quality of graduates who are likely to be placed in positions of important decision making in their professional endeavors. It is more so more important in private universities where employees do not have the kind of job security as is the case in public universities. It is under this background that the study set out to investigate the effects of career guidance on employee performance in Kenyan private universities, with a particular interest in the religious based Private Universities in Kenya. This was a descriptive study design targeting all the employees of religious based private universities in Kenya which included Daystar, CUEA, St. Pauls and KeMU and totaled 2336. The established sample size was 341. The main data collection tool was questionnaires, from which the obtained quantitative data was analyzed by both descriptive and inferential analyses. Results indicate that career guidance is a significant predictor of employee performance) (β =.204, p